PERAN KELEMBAGAAN MANCUANA POPA’ANO DALAM MENJAGA KELESTARIAN HUTAN KAOMBO DI KELURAHAN GONDA BARU KECAMATAN SORAWOLIO KOTA BAU-BAU - Sahril Sahril; La Nalefo; Nur Isiyana Wianti (Fakultas Pertanian Universitas Halu Oleo, 2022)
This study aims to determine the social system in society in Gonda Baru Village. To find out the institutional role of